Effect of Chalazion on Corneal Astigmatism - Ramakrishnan, Abinaya; Veeramani, Panimalar A; G, Taarika (International Journal of Membrane Science and Technology, 2023)
A common eyelid disease chalazion causes eye morbidity due to inflammation and cosmetic disfigurement. Important factors in corneal refractive surgery, intraocular lens power calculations for cataract surgery and visual acuity assessments are corneal topographic changes. For better outcome of ocular surgery corneal astigmatism should be corrected earlier. The aim of this study is to evaluate changes in corneal astigmatism according to chalazion size and location. Methods: This cross-sectional study was conducted in saveetha medical college and hospitals, Thandalam , Department of Ophthalmology Outpatient department. A total of 44 eyes from 33 patients were included in the chalazion group and 70 eyes from 46 patients comprised the control group. Chalazia were classified according to location and size. An autokeratorefractometer and a dual-Scheimpflug analyzer were utilized to evaluate corneal changes. Result: Oblique astigmatism was greater in the chalazion group compared with the control group (p < 0.05). Astigmatism by simulated keratometry (simK), steep K by simK, total root mean square, second order aberration, oblique astigmatism, and vertical astigmatism were significantly greater in the upper eyelid group (p < 0.05). Astigmatism by simK, second order aberration, oblique astigmatism, and vertical astigmatism were significantly greater in the large-sized chalazion group (p < 0.05). Corneal wavefront aberration was the greatest in the upper eyelid chalazion group, whole area group, and large-sized chalazion group (p < 0.05). Conclusions: Large-sized chalazion in the upper eyelid should be treated in the early phase as great changes in corneal topography were noticed. Corneal topography should be performed preoperatively before chalazion is treated.